Thickening of Rubber Sap (Hevea brasilliensis) Through the Utilization of Natural Ingredients Noni Fruit Extract (Morinda citrifolia L.) (Students Field Practice of Human and Environmental Subject) - Muhammad Yassir, (Jurnal Serambi Ilmu, 2024)
The purpose of this study was to increase students' knowledge about the benefits of noni fruit extract (Morinda citrifolia L.) for thickening of rubber latex (Hevea brasilliensis). This research was conducted in 2020 in the village of Terutung Pedi, Babussalam District, Southeast Aceh Regency, The method used in this research is the experimental method with a non-factorial Randomized Block Design (RAK) designed in five treatments and three replications. The tools is the mineral water bottle, blender, notebook, camera, plastic bucket, measuring cup, measuring pipette, knife, filter, stopwatch/Hp and scale. The ingredients is noni fruit (Morinda citrifolia) which is ripe with the characteristics of a white skin and fruit flesh that contains a lot of water and rubber latex (Hevea brasilliensis) that has been tapped. The conclusion was that the administration of noni fruit extract (Morinda citrifolia L.) had a significant effect on the thickening of rubber latex (Hevea brasilliensis).